Perencanaan Strategis Sistem Informasi pada KR Hotel Palembang - Abel De Lando (International Forum of Researchers and Lecturers, 2026)
This study aims to develop a strategic plan for Information Systems and Information Technology (IS/IT) at KR Hotel Palembang by applying the Ward and Peppard methodology. The analysis began with external environment assessment using the PEST framework and internal analysis through the MOST method and Value Chain model. The results were synthesized into a SWOT analysis to identify the organization's strengths, weaknesses, opportunities, and threats. From this, Critical Success Factors (CSF) were formulated to guide the determination of key information system needs. Application portfolio mapping was then conducted using the McFarlan Strategic Grid to classify systems based on their strategic impact. Findings indicate that KR Hotel has strong potential in leveraging digital technologies but faces challenges such as the absence of integrated systems across departments and limited IT training for staff. To address these issues, an integrated system named ZKBiolock was proposed, encompassing modules such as hotel management, financial management, customer relationship management (CRM), human resource training systems, digital promotion, and internal network monitoring and control. This strategic plan is supported by a comprehensive database design, network topology, human resource and infrastructure analysis, investment budgeting, and Return on Investment (ROI) evaluation. The proposed strategy aims to enhance the efficiency and effectiveness of the hotel's operational management.